Generalized anxiety is a predictor of impaired quality of life in patients with atrial fibrillation: findings from the prospective observational ARENA study - Sadlonova, Monika; Salzmann, Stefan; Senges, Jochen; Celano, Christopher M.; Huffman, Jeff C.; Borggrefe, Martin; Akın, Ibrahim; Thomas, Dierk; Schwarzbach, Christopher Jan; Kleemann, Thomas; Schneider, Steffen; Hochadel, Matthias; et al. (Journal of psychosomatic research, 2024)
Objective - Atrial fibrillation (AF) is associated with impaired health-related quality of life (HRQoL), an increased risk of morbidity, and mortality. Traditional AF-related outcomes (e.g., AF recurrence) primarily demonstrate the physiological benefits of AF management but do not focus on the benefits experienced subjectively by the patient (i.e., patient-reported outcomes), which have been suggested as optimal endpoints in AF intervention studies. The aim of this study is to identify medical and psychological factors associated with impaired HRQoL at 1-year follow-up. - Methods - Using data from the prospective observational multicenter ARENA study in patients with AF, we analyzed associations between medical factors, anxiety, and HRQoL at 1-year follow-up assessed using 5-level EuroQoL-5D. - Results - In 1353 AF patients (mean age 71.4 ± 10.3 years, 33.8% female), none of the medical predictors (e.g., heart disease) or history of cardioversion were associated with HRQoL at the 1-year follow-up. Higher generalized anxiety (β = -0.114, p < .001) but not cardiac anxiety (β = -0.006, p = .809) at baseline predicted decreased HRQoL, independent of confounding variables and patients' medical status. Furthermore, the worsening of patients' generalized anxiety was associated with decreased HRQoL (ß = -0.091, p < .001). In contrast, the improvement of generalized anxiety over time predicted higher HRQoL (ß = 0.097, p < .001). Finally, the worsening of patients' cardiac anxiety over time was associated with decreased HRQoL (ß = -0.081, p < .001). - Conclusion - Our results highlight the importance of anxiety as a predictor of future HRQoL in patients with AF. Additional studies to examine the impact of anxiety treatment on HRQoL in this population are needed. - Clinical trial registration - The investigators registered on ClinicalTrials.gov (NCT02978248) on November 30, 2016 https://clinicaltrials.gov/ct2/show/NCT02978248.
Online verfügbar: 8. November 2023, Artikelversion: 16. November 2023
Gesehen am 08.10.2024